Caracterização in vitro do aptâmero A4 selecionado contra células de câncer de próstata - Fernández, Esther Campos (2018)
Aptamer A4 is an RNA oligonucleotide with binding capability to prostate cancer cells that was selected by the Systematic Evolution of Ligands by EXponential enrichment technique in 3D culture (3D Cell-SELEX). The aim of this study was the in vitro characterization of aptamer A4. For this, the profile of viability, proliferation, migration, clonogenicity, cell cycle and expression of genes associated with prostate cancer was assessed in tumor (PC-3) and non-tumor (RWPE-1) prostatic cell lines incubated with aptamer A4. Proliferation, viability, migration and clonogenicity of prostatic cells were not altered after incubation with aptamer A4. However, aptamer A4 altered RWPE-1 cell cycle and gene expression profile of genes related to prostate cancer in PC-3 and RWPE-1 cells. Thus, aptamer A4 could be used in diagnostic systems for prostate cancer, but its use in therapeutic systems requires further studies to understand the changes in cell cycle and gene expression profiles.